Ulasan Naratif pada Penanganan Perundungan Siswa Berbasis Perspektif Konseling Realita - Masbahur Roziqi (Jurnal Psikoedukasi dan Konseling)
The rise of bullying in schools requires primary handling from counselors or guidance and counseling teachers. One urgent approach that can be used to deal with bullying is the reality counseling approach. This study aims to learn how to handle bullying through a reality counseling approach. A method, namely narrative reviews, is also used to collect articles using the Publish and Perish application. The research results of this narrative review are that reality perspective counseling can help perpetrators and victims of bullying develop better and more positively. Apart from that, the reality counseling approach can also collaborate with the culture of each client and counselor's area. In conclusion, the reality counseling approach can be used by counselors in cases of bullying, which are very likely to occur in schools. Counselors and counselees who pay attention to cultural perspectives can use reality counseling to deal with bullying behavior and recover from bullying that victims have experienced.